Prevalence of Latent TB Infection among Health Care Workers in Three Main TB Health Facilities, Baghdad, Iraq, 2013 - Alaa H. Al-Ameri; Petru Armean; Faris Al-Lami (مجلة كلية الطب, 2014)
Background: Tuberculosis infection represents a global health problem and a great risk to Health Care Workers. Identifying individuals, particularly Health Care Workers with latent tuberculosis infection will support tuberculosis control through chemoprophylaxis and prevent cross-infection. The aim of this study was to assess the prevalence and some risk factors for latent tuberculosis infection among Health Care Workers in three tuberculosis health institutions in Baghdad. Methods: A cross-sectional study was conducted in 2013 in Baghdad- Iraq on Health Care Workers working in the Specialized Respiratory & Chest Diseases Center (Tuberculosis institute), Ibn Zuhur Hospital for Chest Diseases and Al-Resafa Health District TB Clinic in Al-Sadr City. Information about age, gender and occupation was obtained. All subjects received a Mantoux tuberculin skin test. Induration of ≥10 mm was considered a positive test. Results: A total of 212 Health Care Workers were enrolled, 71.7% of them were males; none had recently received BCG vaccine. Fifty nine (27.8%) had a positive tuberculin skin test.  Physicians (38.2%) and nurses & paramedicals (31%) have the highest rates of positive result than other occupations. The highest rate of positive results was seen among Health Care Workers in Specialized Respiratory & Chest Diseases Center (55.1%). There was a significant association between positive TST response with the occupation (job title) and the working site. No significant association was seen with age or gender (P>0.05).